Watching Over the Watchdogs: The problems that Filipino journalists face. (2nd January 2017) - Tandoc, Edson C.
Abstract : Studying the problems that journalists face is important, considering the role that journalists play in reporting about and legitimizing the problems that confront society. This study explores what journalists in the Philippines, a young democracy with a unique media ecology, consider to be the most important problem they face. Drawing on a survey of 349 Filipino journalists, this study found that journalists in the Philippines are most concerned about low pay, media violence, information access, and professionalism. Younger journalists tend to identify low pay as the most important problem, while the problem of violence against journalists was more salient for reporters than for editors and managers.